2020
DOI: 10.3389/fphar.2020.569368
|View full text |Cite
|
Sign up to set email alerts
|

Protoporphyrin IX Stimulates Melanogenesis, Melanocyte Dendricity, and Melanosome Transport Through the cGMP/PKG Pathway

Abstract: Protoporphyrin IX (PPIX) is a heterocyclic organic compound that is the last intermediate in the heme biosynthetic pathway. PPIX, due to its photodynamic effects, is utilized in the treatment of skin diseases. Furthermore, PPIX has been utilized as a melanogenesisstimulating agent in various studies. However, the exact function and mechanism underlying PPIX action in melanocytes remain to be elucidated. In the present study, we sought to further investigate how PPIX affects melanocyte melanogenesis, and whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The coculture system of B16F10 and HaCaT cells were established on confocal dish, as described previously ( Lee et al, 2015 ; Lv et al, 2020c ). After J147 treatment, the cells were immunostained with anti-GP100 and anti-Cytokeratin according to the standard protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The coculture system of B16F10 and HaCaT cells were established on confocal dish, as described previously ( Lee et al, 2015 ; Lv et al, 2020c ). After J147 treatment, the cells were immunostained with anti-GP100 and anti-Cytokeratin according to the standard protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Ultraviolet B (UVB) is the strongest exogenous factor that enhances melanin synthesis, 2 and UV‐induced melanogenesis plays a vital role in photoprotection 3 . UV irradiation induces the secretion of α‐melanocyte‐stimulating hormone from keratinocytes; this hormone binds to the melanocortin‐1 receptor in melanocytes to increase intracellular cyclic adenosine monophosphate (cAMP) level, subsequently activating the protein kinase A (PKA)/cAMP‐responsive element‐binding (CREB) pathway to promote melanogenesis 4,5 . Biopsy data have revealed that the expression of melanocyte‐specific markers such as microphthalmia transcription factor (MITF), MART1, Pmel17, tyrosinase and dopachrome tautomerase increases after 1 week of UV exposure 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Melanosomes localize around the cell nucleus through the activity of the endosomal transport system 9 . Developed melanosomes relocate from the perinuclear range to the cell layer by moving along two cytoskeletal components (i.e., microtubules and actin filaments) and are eventually transferred to neighbouring keratinocytes 4 . During this process, Rab27a, myosin Va and melanophilin (Mlph) form a tripartite protein complex involved in the transportation of melanosomes from microtubules to actin fibres 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, because melanin is present on the surface of zebrafish embryos and the process of pigmentation can be easily observed without complicated experimental steps, numerous studies have used zebrafish embryos for melanin-related experiments [9]. Detection of important indicators that affect melanogenesis, such as tyrosinase activity, in the zebrafish embryo model is also feasible [10]. In addition, the appearance of zebrafish embryos and heart rate can also be used to evaluate the toxicity of samples [9].…”
Section: Introductionmentioning
confidence: 99%